Analysis of Black Level Calibration Algorithm for CIS - Yao, Hong Tao; Wang, Zi Qiang; Jiang, Zhen Gang; Gu, Yuan Bao (Applied Mechanics and Materials, 2014)
This paper presents the structure and the operational principle of CMOS image sensors. And then the reason is illuminated for producing dark current and black level of CMOS image sensors. It is necessary to calibrate dark current and black level to improve quality of CMOS image sensors. The dark current is corrected by optimizing pixel structure, perfecting technology, improving 6layout, and correction double sample. But these ways do not calibrate black level. So, it is important to calibrate black level using black level calibration algorithm in the stage of image processing.